Therapeutic potential and mechanisms of mesenchymal stem cell-derived exosomes as bioactive materials in tendon–bone healing - Zou, Jiaxuan; Yang, Weinan; Cui, Wushi; Li, Congsun; Ma, Chiyuan; Ji, Xiaoxiao; Hong, Jianqiao; Qu, Zihao; Chen, Jing; Liu, An; Wu, Haobo (Journal of nanobiotechnology, 2023)
Tendon–bone insertion (TBI) injuries, such as anterior cruciate ligament injury and rotator cuff injury, are the most common soft tissue injuries. In most situations, surgical tendon/ligament reconstruction is necessary for treating such injuries. However, a significant number of cases failed because healing of the enthesis occurs through scar tissue formation rather than the regeneration of transitional tissue. In recent years, the therapeutic potential of mesenchymal stem cells (MSCs) has been well documented in animal and clinical studies, such as chronic paraplegia, non-ischemic heart failure, and osteoarthritis of the knee. MSCs are multipotent stem cells, which have self-renewability and the ability to differentiate into a wide variety of cells such as chondrocytes, osteoblasts, and adipocytes. Numerous studies have suggested that MSCs could promote angiogenesis and cell proliferation, reduce inflammation, and produce a large number of bioactive molecules involved in the repair. These effects are likely mediated by the paracrine mechanisms of MSCs, particularly through the release of exosomes. Exosomes, nano-sized extracellular vesicles (EVs) with a lipid bilayer and a membrane structure, are naturally released by various cell types. They play an essential role in intercellular communication by transferring bioactive lipids, proteins, and nucleic acids, such as mRNAs and miRNAs, between cells to influence the physiological and pathological processes of recipient cells. Exosomes have been shown to facilitate tissue repair and regeneration. Herein, we discuss the prospective applications of MSC-derived exosomes in TBI injuries. We also review the roles of MSC–EVs and the underlying mechanisms of their effects on promoting tendon–bone healing. At last, we discuss the present challenges and future research directions. Graphical Abstract